Inclusion behavior of β-cyclodextrin with bipyridine molecules : factors governing host-guest Inclusion geometries - Yoon, Il. (2011)
The 1:1 complexation of β-cyclodextrin (β-CD) with structurally similar bipyridine guests which lead to the formation of six inclusion complexes (1–6) of β-CD with 4,4′-vinylenedipyridine, 2,2′-vinylenedipyridine, 1-(2-pyridyl)-2-(4-pyridyl)ethylene, 4,4′-ethylene-dipyridine, 4,4′-dithiodipyridine, and 2,2′-dithiodipyridine has been investigated comprehensively by X-ray crystallography in the solid state and by 1H NMR spectroscopy and microcalorimetric titration in aqueous solution. The complex formation constants (KS) for the stoichiometric 1:1 host–guest inclusion complexation of β-CD with the bipyridine derivatives were determined in aqueous solution by microcalorimetry and the host–guest inclusion geometries of the complexes were deduced from 1H ROESY NMR spectroscopy. It transpires that the guest bipyridine molecules are included in the β-CD cavity with a range of different inclusion geometries. In the solid state, the crystal superstructures for the β-CD complexes 1, 4, and 5 are characterized by the triclinic crystal system (space group P1) commensurate with AAAA type supramolecular aggregation. By contrast, the β-CD complexes 2, 3, and 6 display either monoclinic (space group P21) or orthorhombic (space group C2221) crystal systems, characteristic of ABAB type supramolecular aggregation. The results demonstrate that the relative locations of the nitrogen atom positions and the bridge-bond links between the two pyridine rings in these bipyridine guests, not only lead to distinct crystal systems and space groups, but also to different binding geometries and thermodynamical parameters on complexation of the bipyridines with β-CD. The knowledge obtained from this research improves our understanding of the molecular recognition and self-assembly processes exhibited by β-CD, both in the solid state and in aqueous solution.